Atividades do enfermeiro nos sistemas de triagem/classificação de risco nos serviços de urgência: revisão integrativa Revisión integrativa sobre las actividades del enfermero en los sistemas de clasificación de riesgo en servicios de urgencia Activities of the nurse involved in triage/risk classification assessment in emergency services: an integrative review - Aline Marques Acosta; Carmen Lucia Mottin Duro; Maria Alice Dias da Silva Lima (Universidade Federal do Rio Grande do Sul, 2012)
Objetivou-se identificar e avaliar as evidências disponíveis na literatura sobre as atividades do enfermeiro na classificação de risco nos serviços de urgência. Realizou-se uma revisão integrativa, com busca nas bases de dados Science Direct, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrievel System Online (MEDLINE), Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) e Scientific Electronic Library Online (SCIELO). Foram selecionados 22 artigos que atenderam aos critérios de inclusão. Os resultados evidenciaram que as principais atribuições deste profissional são a avaliação do estado de saúde do usuário e a tomada de decisão, processo que necessita de conhecimento clínico e de tempo de experiência. O enfermeiro tem a capacidade de organizar o fluxo dos usuários conforme a prioridade do atendimento e a demanda dos serviços, sendo um profissional de excelência na execução da triagem/classificação de risco nos serviços de urgência. Se objetivó identificar y evaluar la evidencia disponible en la literatura sobre las actividades de enfermeros en sistemas de clasificación de riesgo en servicios de urgencia. Se realizó revisión integradora, con búsqueda en las bases Science Direct, Cumulative Índex to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrievel Sistem Online (MEDLINE), Literatura Latinoamericana y del Caribe en Ciencias de la Salud (LILACS) y Scientific Electronic Library Online (SCIELO). Se seleccionaron 22 artículos que cumplieron los criterios de inclusión. Los resultados evidenciaron que las principales atribuciones del profesional son la evaluación del estado de salud del paciente y la toma de decisiones, proceso que necesita conocimiento clínico y tiempo de experiencia. El enfermero tiene la capacidad de organizar el flujo de usuarios de acuerdo con la atención prioritaria y la demanda de servicios, siendo un profesional de excelencia en la ejecución de la clasificación de riesgo en servicios de urgencia. This present study aimed at identifying and assessing available literature regarding the activities of the nurse involved in assessing risk classification in emergency services. The integrative review carried out searches in the following databases: Science Direct, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE), Latin-American and Caribbean Health Sciences Database (LILACS), and Scientific Electronic Library Online (SCIELO). Twenty-two articles that met inclusion criteria were selected. Results indicated that the major attributions of this professional are the assessment of the patient's healthcare status and decision-making, a process that demands clinical knowledge and experience. The nurse is capable of organizing the workflow of patients according to the priority of the rendered care and service demands, and stands out as a professional of excellence in the development of triage/risk classification practices in emergency services.